2016
DOI: 10.1016/j.surg.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Patient autonomy–centered self-care checklist reduces hospital readmissions after ileostomy creation

Abstract: Background Patients who undergo colorectal surgery with new ileostomies incur high rates of readmission. Ostomates face a steep learning curve to master the skills and knowledge needed for success at home. We designed and implemented a patient-centered checklist promoting independence and validating self-care knowledge and care skills, and evaluated its effect on readmissions after ileostomy creation. Methods On a single inpatient unit, new ileostomy patients were taught and evaluated using a novel postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 18 publications
2
53
0
7
Order By: Relevance
“…Overall incidence rates of complications vary from 21% to 60%. 21 Understanding long-term and persistent ostomy-specific concerns and adaptations in CRC survivors can provide information for developing comprehensive supportive care strategies for this understudied cancer population.…”
Section: Ostomy Effects On Patents' Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Overall incidence rates of complications vary from 21% to 60%. 21 Understanding long-term and persistent ostomy-specific concerns and adaptations in CRC survivors can provide information for developing comprehensive supportive care strategies for this understudied cancer population.…”
Section: Ostomy Effects On Patents' Lifementioning
confidence: 99%
“…7 There is growing interest in promoting stoma self-care efficiency to fight common challenges associated with ostomy creation. 21…”
Section: Ostomy Effects On Patents' Lifementioning
confidence: 99%
“…With patient compliance, these programs have shown reductions up to 50% in complications, and 42% in mortality in patients [7,19]. Further, one study having designed and implemented a patient checklist after colorectal surgery showed reduction of readmissions from 28% to 20% [16]. These findings might indicate that introducing a patient checklist before and after surgery can inform patients better about what they can do to prevent complications and enhance their safety knowledge.…”
Section: Introductionmentioning
confidence: 98%
“…Systematic literature reviews on patient involvement in safety show that patients have an important role on their own safety, but evidence on effects of such involvement is limited [3,11,12]. There have been numerous attempts to facilitate use of patient-centred checklist pamphlets and apps [13][14][15][16]. These tools are often not aligned with different hospital administrative systems and the patients' medical records, limiting their potential as communication tools to prevent errors [17].…”
Section: Introductionmentioning
confidence: 99%
“…the list developed by Sullivan and Castleberry [8,9]. Also, checklists developed for postoperative patient education can lead to a significant re-admission rate reduction in patients with ileostomy [10].…”
Section: Discussionmentioning
confidence: 99%